Antiatherogenic Effects of Quercetin in the THP-1 Macrophage Model In Vitro, With Insights Into Its Signaling Mechanisms Using In Silico Analysis - Etimad A. Huwait; Etimad A. Huwait; Salma Y. Saddeek; Salma Y. Saddeek; Salma Y. Saddeek; Rehab F. Al-Massabi; Rehab F. Al-Massabi; Rehab F. Al-Massabi; Sanaa J. Almowallad; Sanaa J. Almowallad; Sanaa J. Almowallad; Peter Natesan Pushparaj; et al. (Frontiers Media S.A., 2021)
Background: Atherosclerosis (AS), a major risk factor for stroke and brain tissue destruction, is an inflammatory disease of the blood vessels, and the underlying pathology is inflammation mediated by various chemokines and cytokines. Quercetin, a natural flavonol, is reported to have both anti-inflammatory and antioxidant properties. As such, in the present study, we evaluated the antiatherogenic effects of quercetin in a human THP-1 cell line in vitro and also the signaling mechanisms using in silico analysis.Materials and Methods: THP-1 macrophages exposed to different concentrations of quercetin (5-100 μM for 24 h) were tested for cytotoxicity. Real-time gene expression assay for intercellular adhesion molecule-1 (ICAM-1) and monocyte chemoattractant protein-1 (MCP-1) was carried out following treatment with quercetin at 15 and 30 μM for 24 h either in the absence or presence of interferon (IFN-γ) for 3 h to induce inflammation. Monocyte migration and cholesterol efflux were also assessed.Results: Quercetin did not exert any cytotoxic effects on THP-1 cells at the various concentrations tested. The gene expression assay showed a significant decrease in ICAM-1 (by 3.05 and 2.70) and MCP-1 (by 22.71 and 27.03), respectively. Quercetin at 15 µM decreased THP-1 monocyte migration by 33% compared to the MCP-1-treated cells. It also increased cholesterol efflux significantly by1.64-fold and 1.60-fold either alone or in combination with IFN-γ, respectively. Ingenuity Pathway Analysis of the molecular interactions of quercetin identified canonical pathways directly related to lipid uptake and cholesterol efflux. Furthermore, CD36, SR-A, and LXR-α also demonstrated significant increases by 72.16-, 149.10-, and 29.68-fold, respectively.Conclusion: Our results from both in vitro and in silico studies identified that quercetin inhibited the THP-1 monocyte migration, MCP-1, and ICAM-1 and increased cholesterol efflux probably mediated via the LXR/RXR signaling pathway. Therefore, quercetin will help prevent cell infiltration in atherosclerotic plaques and reduce the risk of stroke or brain destruction.